2018
DOI: 10.4028/www.scientific.net/msf.916.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Oxidation and Carbon Concentrations on Co-Cr-Mo Alloy in Enhanced Corrosion Protection

Abstract: Surface modification of metallic implants is often required to facilitate positive interaction between the implant and the surrounding hard tissue. In the present study, an oxide layer (Cr2O3) was successfully created on a Co-Cr-Mo alloys substrate by using thermal oxidation technique in atmospheric condition. The effect of different carbon content (0.03% and 0.24%) of oxidized Co-Cr-Mo alloys was investigated in terms of its corrosion behavior using electrochemical impedance spectroscopy techniques that immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several researchers tried to solve this issue using surface modification methods such as physical vapour deposition [ 3 ], chemical vapour deposition [ 4 ], thermal oxidation [ 5 ], Sol-gel [ 6 ], and ion implantation [ 7 ]. Previous studies revealed that most researchers used chemical, mechanical, and physical methods to improve corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers tried to solve this issue using surface modification methods such as physical vapour deposition [ 3 ], chemical vapour deposition [ 4 ], thermal oxidation [ 5 ], Sol-gel [ 6 ], and ion implantation [ 7 ]. Previous studies revealed that most researchers used chemical, mechanical, and physical methods to improve corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%